OCA/OCP Oracle Database 11g All-in-One Exam Guide (Exam 1Z0-051, 1Z0-052, and 1Z0-053) - Watson, John; Ramklass, Roopesh (New York McGraw-Hill, 2010)
Prepare for the Oracle Certified Associate Administration I and SQL Fundamentals I exams and the Oracle Certified Professional Administration II exam with help from this exclusive Oracle Press guide. In each chapter, you'll find challenging exercises, practice questions, and a two-minute drill to highlight what you've learned. This authoritative guide will help you pass the test and serve as your essential on-the-job reference. Get complete coverage of all objectives for exams 1Z0-051, 1Z0-052, and 1Z0-053, including
Three full practice exams
12
Keywords: Electronic data processing personnel -- Certification -- Study guides; Relational databases -- Examinations -- Study guides; SQL (Computer program language) -- Examinations -- Study guides